PURPOSIVE DETERMINATION OF THE DEVELOPMENT OF THE LEGAL SYSTEM - Malyshev Борис Владимирович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
This article contains characteristics of internal and external purposes of the legal system, which serve the cause of its development. External purposes of the legal system are the moral values, ideals of social consciousness (justice, equality, freedom, humanism), and internal purposes are the legal values, ideals (priority of defined in positive law natural rights and the rule of law).